(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Every 6th person in the world today is an Indian. Our country supports more than 17 of theworld’s population. This is one of the biggest challenges but also contains a hidden opportunity for ourcountry. If this large manpower is converted into human capital i.e. human resources it can prove to bean asset for the country rather than a liability. Human resource means the size of the population of acountry along with its efficiency, educational qualities, productivity, organisational abilities andfarsightedness.India has been categorised by the Human Development Report of 2020 as a medium human- developedcountry. There is an urgent need to take care of our large manpower otherwise the problem of hunger,malnutrition, poverty and unemployment will multiply. These chronic problems can be tackled to someextent by providing proper health care facilities and adequate educational facilities. Unfortunately, oureducation system has become a factory of producing degree holders. There is a dire need to reconstructour education system. Dr. S. Radhakrishnan said “The three things-vital dynamism, intellectualefficiency and spiritual direction together constitute the proper aim of education. Moral and spiritualtraining is an essential part of education.” The education we provide should help them to appreciate ourcultural heritage and values to develop their values and the value system will guide them in their personaland social life and will form the foundation of the society we dream of. This paper attempts to highlightthe importance of education more specifically value education in making this world a better place to livein. By enriching human resources in this way a humane world can be created where we can realiseuniversal sisterhood and brotherhood i.e. Vashudhaiva Kutumbakam.